Nanostructured Ba/ZnO modified electrode as a sensor material for detection of organosulfur thiosalicylic acid - Shanbhag M.M.; Shetti N.P.; Kulkarni R.M.; Chandra P. (My University, 2025)
Electrochemical sensors are regulated by the interaction of several chemical solutions to generate an electrical signal proportional to the concentration of the analytes. A novel electrochemical sensor is reported in this study for an organosulfur molecule, thiosalicylic acid (TSA) detection by the casting of electro-catalytic barium doped zinc oxide nanoparticle suspension on a glassy carbon electrode (GCE). The electrochemical response of TSA was examined simultaneously for bare GCE and electro-chemically modified GCE, i.e. Barium doped zinc oxide nanoparticle/GCE (BDZONPs/GCE) by utilizing different voltammetric techniques in an acidic medium of pH 3.0. In comparison with the bare GCE, the modified GCE exhibits a decent response towards oxidation of TSA with a well-defined peak current. The catalytic nature, conducting nature, and large surface area of the nanoparticles which influences the remarkable enhancement of the TSA at BDZONPs/GCE was examined. The impact of accumulation time, pH dependency, and the scan rate variation were also studied. Based on the experimental data the physicochemical parameters were being calculated. The sensitive squarewave voltammetry (SWV) was used to monitor the low detection limit of TSA. Applicability of proposed work showed good sensitivity, selectivity, and noticeable recovery results with BDZONPs/GCE. © 2020 Elsevier B.V.